'Care Under Pressure': a realist review of interventions to tackle doctors' mental ill-health and its impacts on the clinical workforce and patient care. Issue 2 (2nd February 2018) - Carrieri, Daniele; Briscoe, Simon; Jackson, Mark; Mattick, Karen; Papoutsi, Chrysanthi; Pearson, Mark; Wong, Geoffrey
Abstract : Introduction: Mental ill-health is prevalent across all groups of health professionals and this is of great concern in many countries. In the UK, the mental health of the National Health Service (NHS) workforce is a major healthcare issue, leading to presenteeism, absenteeism and loss of staff from the workforce. Most interventions targeting doctors aim to increase their 'productivity' and 'resilience', placing responsibility for good mental health with doctors themselves and neglecting the organisational and structural contexts that may have a detrimental effect on doctors' well-being. There is a need for approaches that are sensitive to the contextual complexities of mental ill-health in doctors, and that do not treat doctors as a uniform body, but allow distinctions to account for particular characteristics, such as specialty, career stage and different working environments. Methods and analysis: Our project aims to understand how, why and in what contexts support interventions can be designed to minimise the incidence of doctors' mental ill-health. We will conduct a realist review—a form of theory-driven interpretative systematic review—of interventions, drawing on diverse literature sources. The review will iteratively progress through five steps: (1) locate existing theories; (2) search for evidence; (3) select articles; (4) extract and organise data and (5) synthesise evidence and draw conclusions. The analysis will summarise how, why and in what circumstances doctors' mental ill-health is likely to develop and what can remediate the situation. Throughout the project, we will also engage iteratively with diverse stakeholders in order to produce actionable theory. Ethics and dissemination: Ethical approval is not required for our review. Our dissemination strategy will be participatory. Tailored outputs will be targeted to: policy makers; NHS employers and healthcare leaders; team leaders; support organisations; doctors experiencing mental ill-health, their families and colleagues. PROSPERO registration number: CRD42017069870 .